EL DEMONIO DE LA SUPERPOBLACIÓN - Ludi Simpson (Astrolabio: Nueva Época, 2012)
Population growth is often blamed for poverty and environmental disaster both globally and locally. Unjustified fears of either excessive population growth or continuous population decline have been identified as a continuing feature of human society. The paper examines the claim of over-population as put by an active campaign for restrictive population policies. It briefly reviews reports on food and environmental sustainability, which show capacity to accommodate UN projections of further population growth. Considering the historical and social context of claims of detrimental impact of population size, the claims appear to be a distraction from population behaviour. Regulation of detrimental behaviour is required for effective reduction of environmental threats and to reduce inequality.